Religionskundliches Unterrichtswerk - Kesseler, Kurt; Oppermann, Wilhelm; Schremmer, Bruno (Verlag von Quelle & Meyer, 1931)
Thematisch geordnete Bibelsprüche, Luthers kleiner Katechismus, Lieder, Gebete